2024
DOI: 10.5114/aoms/182886
|View full text |Cite
|
Sign up to set email alerts
|

Trends of ischemic heart disease mortality attributable to smoking in the five countries with the highest number of smokers during 1990–2019: an age-period-cohort analysis

Shaoliang Tang,
Juan Meng,
Xinghua Zhao
et al.

Abstract: IntroductionSmoking increases the risk of various cardiovascular diseases, including ischemic heart disease (IHD). This study aimed to assess the impact of age, period, and cohort on long-term trends in IHD mortality in China, India, Indonesia, the United States, and Russia, the five countries with the highest number of smokers, from 1990 to 2019.Material and methodsThe data were obtained from the Global Burden of Disease (GBD) Study 2019, and the age-standardized mortality rate (ASMR) was calculated. Joinpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Our research findings underscore the imperative need to reinforce smoking control policies and diminish public exposure to SHS 28 . The comprehensive enforcement of indoor smoking bans and public education campaigns to elevate awareness of the hazards associated with SHS exposure constitutes a pivotal strategy for safeguarding public health and alleviating healthcare burdens 5 , 29 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our research findings underscore the imperative need to reinforce smoking control policies and diminish public exposure to SHS 28 . The comprehensive enforcement of indoor smoking bans and public education campaigns to elevate awareness of the hazards associated with SHS exposure constitutes a pivotal strategy for safeguarding public health and alleviating healthcare burdens 5 , 29 .…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, fostering smoke-free environments and providing readily accessible smoking cessation support services, such as counseling and nicotine replacement therapies, are crucial for facilitating smokers’ quitting efforts 20 , 30 . This multifaceted approach demands the collaborative involvement of government agencies, community organizations, and the wider public to foster a healthier living environment and reduce the risk of diseases such as IHD 28 , 31 . In our study, we also observed that the decline in mortality rates among men and the older age groups is slower, and there is a continuous increase in the DALYs rates among the elderly population in middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…This process is caused by more than 7000 chemicals found in cigarettes, such as tar, nicotine, and carbon monoxide. These chemicals can cause cardiovascular disease by increasing heart rate and myocardial contractility, promoting inflammation, causing endothelial damage and thrombosis, and lowering serum high-density lipoprotein cholesterol levels [18][19][20] . Inflammation plays an Each black point represents an inverse variance weighted method for estimating the effect of smoking initiation on atrial fibrillation, excluding that particular instrumental variable from the analysis.…”
Section: Discussionmentioning
confidence: 99%